Cardiovascular changes in patients with non-severe Plasmodium vivax malaria - Alencar-Filho, Aristoteles Comte; Ferreira, Joao Marcos Bemfica Barbosa; Salinas, Jorge Luis; Fabbri, Camila; Monteiro, Wuelton Marcelo; Siqueira, Andre Machado; Okoshi, Katashi [UNESP]; Lacerda, Marcus Vinicius Guimaraes; Okoshi, Marina Politi [UNESP] (Elsevier, 2016)
Background: Cardiovascular system involvement in patients with Plasmodium vivax malaria has been poorly addressed. The aim of this study was to evaluate cardiac structures and function, and serum markers of cardiovascular injury in patients with the non-severe form of vivax malaria in Manaus, Amazonas State, Brazil. Methods and results: We prospectively evaluated 26 patients with vivax malaria in an outpatient referral hospital and compared results with a control group of 25 gender- and age-matched healthy individuals. Patients underwent clinical evaluation, laboratory tests, and transthoracic echocardiography at first evaluation (day zero, D0) and seven days (D7) after malaria diagnosis. At D0 echocardiography showed higher left ventricular (LV) systolic diameter (28.8 ± 2.82 vs 30.9 ± 4.03 mm; p = 0.037) and LV diastolic volume (82.4 ± 12.3 vs 93.8 ± 25.9 ml; p = 0.05), and lower LV ejection fraction (Teicholz method: 73.2 ± 6.59 vs 68.4 ± 4.87%; p = 0.004) in patients compared to controls. Right ventricle (RV) fractional area change (54.7 ± 5.11 vs 50.5 ± 6.71%; p = 0.014) was lower, and RV myocardial performance index (0.21 ± 0.07 vs 0.33 ± 0.19; p = 0.007), and pulmonary vascular resistance (1.13 ± 0.25 vs 1.32 ± 0.26 Woods unit; p = 0.012) were higher in patients than controls. Patients presented higher serum levels of unconjugated bilirubin (0.24 ± 0.15 vs 1.30 ± 0.89 mg/dL; p < 0.001), soluble vascular cell adhesion molecule-1 (sVCAM-1; 453 ± 143 vs 1983 ± 880 ng/mL; p < 0.001), N-terminal prohormone brain natriuretic peptide (0.59 ± 0.86 vs 1.08 ± 0.81 pg/mL; p = 0.045), and troponin T (861 ± 338 vs 1037 ± 264 pg/mL; p = 0.045), and lower levels of plasma nitrite (13.42 ± 8.15 vs 8.98 ± 3.97 μM; p = 0.016) than controls. Most alterations had reversed by D7. Conclusion: Patients with non-severe Plasmodium vivax malaria present subclinical reversible cardiovascular changes.
Keywords: Echocardiogram; Myocardial injury; Prognosis; Pulmonary artery pressure; Right ventricle; Ventricular function